Теорія і робочі процеси гідравлічних обертачів планетарного типу: автореф. дис….доктора техн. наук - Волошина, Анжела Анатоліївна; Voloshyna, Anzhela (My University, 2012)
Диссертация посвящена усовершенствованию теории расчета и проектирова- ния рабочих поверхностей вытеснительной и распределительной систем гидровра- щателя планетарного типа на базе исследования их рабочих процессов. Разработаны научные положения, позволяющие формировать подходы и принципы математиче- ского моделирования, направленные на улучшение выходных характеристик гид- равлических вращателей планетарного типа в составе гидроагрегатов приводов мо- бильной техники путем разработки рекомендаций по расчету и проектированию их распределительных и вытеснительных систем. /////////////// The dissertation is devoted to research of the working processes of displacing and distributing systems, output characteristics of hydraulic rotators of planetary type on the basis of their full mathematical models development. The developed mathematical model of a planetary hydraulic rotator as a part of the hydraulic unit allows to investigate dynam- ic processes which take place in its elements taking into account design features of dis- placing and distributing systems of a planetary hydraulic rotator. The developed mathe- matical model of the hydraulic unit with the planetary hydraulic rotator with the driving engine and elastic and inertial loading considers the equations of expenses and continuity of a stream on the basis of system approach where hydraulic units (including working liq- uid) are considered in interrelation as a whole. The developed unified rotators range and design documentation for production of hydraulic rotators of planetary type with working volumes of 4000, 5000, 6300 and 8000 cm3 applied in hydraulic drives of active working tools of mobile machinery allow to reduce its steel intensity, power expenses and also to reduce time for its designing. The developed classification of hydraulic machines of volu- metric action with a cycloidal form of displacers depending on their constructive and func- tional characteristics will allow to make a choice of optimum schemes of planetary hy- draulic machines for an active working tools drive while mobile machinery designing.
Theory and working processes of hydraulic rotators of planetary type.
Keywords: the hydraulic unit; hydraulic rotator of planetary type; displacing and distributing systems; working processes; an operating clearance; running parts; transients, dynamics; mechanical; volumetric and general efficiency; the unified range; hydraulic